Philippines : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2007)
The 2006 Article IV Consultation on the Philippines discusses stronger exports and reduced inflation, with the 12-month rate back within the inflation target. Remittances have continued to grow strongly, and the balance of payments received additional support in the second half of 2006 from weaker oil prices. Continued reforms are necessary to boost investment and accelerate progress in reducing poverty. Executive Directors observed that stock of repossessed real estate assets remains large and that solving this problem will be key to allowing the banking sector to contribute to investment recovery.